Human Milk to Protect from Respiratory Infections. Issue 3 (May 2023) - Spatz, Diane L.
Abstract : This past winter, media covered the high levels of the flu, respiratory illnesses, and respiratory syncytial virus (RSV), with hospitals being strained and at capacity. Our breastfeeding expert, Dr. Spatz, discusses the evidence about exclusive breast milk feeding and protection against respiratory viruses.